Public Information Disclosure Communication Strategy at the Regional Liaison Agency of Banten Province - Laksana, Muhibudin Wijaya; Alia, Siti; Nuraeni, Rina (Jurnal Ilmu Administrasi Negara (JUAN), 2024)
The study investigates the communication strategy of the Regional Liaison Agency (BPD) of Banten Province in implementing Public Information Disclosure (KIP) policies, motivated by its classification as an "informative" institution in 2021. Using Harold Lasswell's communication theory, this descriptive qualitative research employs observation, interviews, and documentation analysis, analyzed through Miles and Huberman's interactive techniques. The findings reveal that BPD's strategy involves appointing Information and Documentation Management Officers (PPID) as communicators, segmenting messages according to KIP Law requirements, and tailoring media use to audience characteristics. BPD utilizes websites, social media, brochures, and public information desks to disseminate information, achieving effective outreach and audience engagement. Challenges include limited budget allocation, insufficient human resources, misperceptions about BPD's role, and the agency's location outside the Banten Province, which hinder communication efforts. The study concludes that while the implemented strategies are effective, addressing these barriers is essential for optimizing public service delivery and enhancing institutional accountability. This research contributes to the literature on policy communication, emphasizing the critical role of strategic communication in governance.